Darier's Disease Flare following COVID-19 Vaccine - Mette Vestergaard Elbæk; Gabrielle Randskov Vinding; Gregor Borut Ernst Jemec (Karger Publishers, 2021)
Darier's disease is a rare genodermatosis characterized clinically by dyskeratotic papules in the seborrheic and intertriginous areas and nail abnormalities. Dyskeratosis and acantholysis are typical histological findings. Darier's disease is not known to be inflammatory by nature as inflammation occurs primarily due to local infections, and it may therefore differ from inflammatory dermatoses such as psoriasis and cutaneous lupus in response to antigen stimulation. Known triggers of Darier's disease primarily include exogenous factors such as sun exposure, friction, or infection. We present a case of a 47-year-old white female with a flare of Darier's disease 2 days following her first vaccination with COVID-19 vaccine (ChAdOx1-s [recombinant]) (Vaxzevria® [previously known as COVID-19 vaccine AstraZeneca]). In this case report, we discuss possible mechanisms linking the vaccination and the flare of Darier's disease. We consider inflammatory mechanisms as well as a random co-occurrence. Due to the close time-related association between the disease flare and the COVID-19 vaccination, we find an urge to make other clinicians aware of a possible association.